2007
DOI: 10.1038/sj.mp.4001995
|View full text |Cite
|
Sign up to set email alerts
|

The discoidin domain receptor 1 as a novel susceptibility gene for schizophrenia

Abstract: Evidence suggests that myelin alterations could predispose to schizophrenia. Reduced expression of several myelin genes has been observed in schizophrenia patients. Recently, we identified the discoidin domain receptor 1 (DDR1; located at human chromosome 6p21.3) as a myelin gene in the mouse model and in a human oligodendroglial cell line. In the present study we screened for single nucleotide polymorphisms (SNPs) in the DNA from 100 schizophrenia patients. We identified a novel mutation within exon 10 that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 56 publications
(52 reference statements)
2
34
1
Order By: Relevance
“…Even though previous studies contradict our finding (6)(7)(8)(9)(10)21,22), these studies nevertheless suggested that the DDR1 gene participates in the development and progression of diseases, such as, auto-inflammatory and renal diseases.…”
Section: ------------------------------------------------------------contrasting
confidence: 55%
See 2 more Smart Citations
“…Even though previous studies contradict our finding (6)(7)(8)(9)(10)21,22), these studies nevertheless suggested that the DDR1 gene participates in the development and progression of diseases, such as, auto-inflammatory and renal diseases.…”
Section: ------------------------------------------------------------contrasting
confidence: 55%
“…DDR1 is a possible susceptibility marker of diseases other than renal diseases, such as schizophrenia, ovarian cancer, juvenile oligoarthritis, hearing loss, Churg-Strauss syndrome, small cell lung carcinoma, and endometrial cancer (6)(7)(8)(9)(10)21,22). Notably, in one study on schizophrenia (9), in which rs1049623 was found to be a susceptibility marker, but this SNP was found to have no significance in the present study.…”
Section: ------------------------------------------------------------mentioning
confidence: 70%
See 1 more Smart Citation
“…The gene that encodes prolactin (PRL) has been mapped to chromosome 6p21 (Evans, 1989;Owerbach et al, 1981). The 6p21 region has been identified as a susceptibility locus that harbors genes associated with schizophrenia (Roig et al, 2007;Schwab et al, 2003;Tochigi et al, 2004). A recent genome-wide analysis (Stefansson et al, 2009) also found that this region was significantly associated with schizophrenia.…”
Section: Introductionmentioning
confidence: 92%
“…It seems counterintuitive that reduction in miR-219 appears to be responsible for hyperactivity in the acute dizocilpine paradigm but reducing miR-219 levels with antisense infusion reverses dizocilpine-induced hyperactivity. Despite these inconsistencies, it is important to note that the gene for miR-219 implicated by Kocerha et al (2) is located at 6p21, which is a putative susceptibility locus for schizophrenia (5).…”
mentioning
confidence: 99%